Lactate dehydrogenase to albumin ratio (LAR) is a novel predictor of fatal outcome in patients with SFTS: an observational study - Meng, Tao; Ding, Wenqian; Lv, Dongmei; Wang, Chenxu; Xu, Yuanhong (Frontiers in Public Health, 2024)
BackgroundSevere fever with thrombocytopenia syndrome (SFTS) is a serious infectious disease. This study explored the prognostic value of lactate dehydrogenase (LDH) to albumin (ALB) ratio (LAR) levels in fatal outcomes of the disease.MethodsTwo-hundred and nine patients with SFTS were enrolled in this study. Based on the prognosis, patients were divided into survival and deceased groups. Laboratory metrics were compared by univariate Cox regression and multivariate Cox regression analyses. The prognostic risk factors for SFTS disease were discussed, and the receiver operator characteristic (ROC) curve and the Kaplan–Meier survival curve were plotted to analyze the predictive value of independent risk factors on disease prognosis.ResultsA total of 209 patients with SFTS, including 152 in the survival group and 57 in the death group, were enrolled. The median age of 209 SFTS patients was 64 years. Three indicators, age, aspartate aminotransferase (AST), and LAR, were identified as predictors of mortality in patients with SFTS. The area under the ROC curve of LAR was the highest (0.835), followed by that of AST (0.794), and age (0.720). The Kaplan–Meier survival curve showed an increased case fatality rate, of >1.4691, in patients with LAR.ConclusionElevated LAR level on admission is an independent risk factor for fatal outcomes in patients with SFTS; this can help healthcare professionals identify patients with SFTS having a high risk of fatal outcomes.